Accuracy and Reliability of Whole Blood Bilirubin Measurements Using a Roche Blood Gas Analyzer for Neonatal Hyperbilirubinemia Screening and Risk Stratification - Wang, Qing; Zhang, Tianyi; Lin, Yuanxi; Jiang, Li; Zhou, Wenlong; Zong, Xiaolong (Frontiers in Pediatrics, 2022)
Abstract Background: Accurate blood bilirubin measurements are essential for appropriate management of neonatal hyperbilirubinemia. This study aimed to evaluate the accuracy and reliability of whole-blood bilirubin measurements obtained using a Roche blood gas analyzer (Roche TBiL), with the total serum bilirubin measurements determined by the Ortho VITROS 4600 chemistry system (Ortho TSB) serving as a reference. Materials and Methods: The medical records of hospitalized neonates that underwent simultaneous Roche TBiL and Ortho TSB measurements were reviewed for eligible population selection and data collection. The correlations and differences between the two sets of results were determined using Passing–Bablok regression analysis and a Bland–Altman plot. For eligible newborns, the risk of developing severe hyperbilirubinemia was calculated using the Bhutani nomogram. Weighted kappa analysis was used to evaluate the agreement between risk prediction by the two methods. Results: We obtained 618 paired Roche TBiL and Ortho TSB results from 309 neonates for consistency evaluation. Roche TBiL and Ortho TSB measurements showed a good correlation (r = 0.951; 95% CI: 0.939–0.961). Passing–Bablok regression analysis yielded the following equation: Roche TBiL = 0.793 × Ortho TSB + 21.198 µmol/L, with a slope of 0.793 (95% CI: 0.762–0.824) and intercept of 21.199 (95% CI: 17.808–24.399). The average difference between the two methods was 1.64 ± 24.84 μmol/L. A total of 207 neonates were eligible for evaluation of the agreement between the risk-grading methods. Although kappa analysis showed good agreement between the methods, with a weighted kappa of 0.681 (95% CI: 0.610–0.751) across all populations, the values for approximately half of the neonates at intermediate and high risk of hyperbilirubinemia (33/72) were underestimated by Roche TBiL. Conclusion: Our results indicate that Roche TBiL and Ortho TSB measurements in the neonatal population are not consistent. As a point-of-care and trace blood assay, Roche blood gas bilirubin measurement can facilitate primary screening of neonatal hyperbilirubinemia, but it cannot be used for risk stratification or clinical decision-making.